Ideas fundacionales, bases académicas y propuesta curricular innovadora de la carrera de odontología, facultad de medicina, Universidad de la Frontera, Chile - Fuentes, Ramón; Henriquez, Jorge; Matamala, Fernando; Mardones, Daniel (Revista Estomatología, 1996)
We inform here about the main curricular aspects on the Dental Branch of the School of Medicine, University La Frontera , Temuco, Chile. We do mentionthe different entites involved in their creation and we also describe as the 4 curricular lines in the curricular net are devided furtherer the integration unit as emphasize an integrator and articulator center. We outline public health distribution and prevention together at a morphological sciencies perspective. We also describe the importance and orientation at the assistence teaching service program ofthe Dental Department fram the Health Ministery. The residence year will be as teaching-assistence, urban and country dedicated to children and adults assistence.